Expression of metalloproteinases MMP-2 and MMP-9 is associated to the presence of androgen receptor in epithelial ovarian tumors - Flavia Morales-Vásquez; Rocío Castillo-Sánchez; María J. Gómora; Miguel Ángel Almaraz; Enrique Pedernera; Delia Pérez-Montiel; Elizabeth Rendón; Horacio Noé López-Basave; Edgar Román-Basaure; Sergio Cuevas-Covarrubias; Juan Maldonado-Cubas; Antonio Villa; et al. (BMC, 2020)
Abstract Background The current study evaluated the metalloproteinases MMP-2 and MMP-9 expression in epithelial cells and the surrounding stroma in ovarian tumors and the association of MMPs with the histological subtypes, the clinical stage and the presence of steroid hormone receptors. Tumor samples were obtained from 88 patients undergoing surgical cytoreduction of primary ovarian tumors in Instituto Nacional de Cancerología, from México City. The formalin fixed and paraffin embedded samples were processed in order to demonstrate the presence of androgen receptor,estrogen receptor alpha, progesterone receptor, MMP-2,MMP-9 and collagen IV by immunohistochemistry and/or immunofluorescence. Results MMP-2 and MMP-9 were differentially expressed in the epithelium and the stroma of ovarian tumors associated to histological subtype, clinical stage and sexual steroid hormone receptor expression. Based on Cox proportional hazard regression model we demonstrated that MMP-2 located in the epithelium and the stroma are independent prognostic biomarkers for overall survival in epithelial ovarian tumors. Kaplan Meir analysis of the combination of AR (+) with MMP-2 (+) in epithelium and AR (+) with MMP-2 (−) in stroma displayed a significant reduction of survival. Conclusions The presence of MMP-2 in the stroma of the tumor was a protective factor while the presence of MMP-2 in the epithelium indicated an adverse prognosis. The presence of AR associated with MMP-2 in the tumor cells was a risk factor for overall survival in epithelial ovarian cancer.